Epigenetic regulation of cutaneous T-cell lymphoma is mediated by dysregulated lncRNA MALAT1 through modulation of tumor microenvironment - Guo, Wei; Liu, Guang-Ming; Guan, Ji-Yu; Chen, Yu-Jia; Zhao, Yang-Zhi; Wang, Kun; Bai, Ou (Frontiers in Oncology, 2022)
Cutaneous T-Cell Lymphoma (CTCL) is a rare non-Hodgkin lymphoma marked by migration of T-lymphocytes to the skin. It has many subtypes some of which are aggressive with documented metastasis. We investigated a possible role of lncRNA MALAT1 in CTCL cells because of its documented involvement in cancer metastasis. A screening of MALAT1 in CTCL patients revealed its elevated levels in the patients, compared to healthy individuals. For our investigation, we employed HH and H9 CTCL cells and silenced MALAT1 to understand the MALAT1 mediated functions. Such silencing of MALAT1 resulted in reversal of EMT and inhibition of cancer stem cell phenotype, along with reduced cell growth and proliferation. EMT reversal was established through increased E-cadherin and reduced N-cadherin while inhibition of cancer stem cell phenotype was evident through reduced Sox2 and Nanog. CTCL patients had higher circulating levels of IL-6, IL-8, IL-10, TGFβ, PGE2 and MMP7 which are factors released by tumor-associated macrophages in tumor microenvironment. MALAT1 sponged miR-124 as this tumor suppressive miRNA was de-repressed upon MALAT1 silencing. Moreover, downregulation of miR-124 attenuated MALAT1 silencing effects. Our study provides a rationale for further studies focused on an evaluation of MALAT1-miR-124 in CTCL progression.